Eighteen Years of Respiratory Syncytial Virus Surveillance. Issue 9 (September 2015) - Bruden, Dana J.T.; Singleton, Rosalyn; Hawk, Carolyn S.; Bulkow, Lisa R.; Bentley, Stephen; Anderson, Larry J.; Herrmann, Leslie; Chikoyak, Lori; Hennessy, Thomas W.
<x xml:space="preserve">Abstract</x> Background: Alaska Native infants from the Yukon-Kuskokwim Delta (YKD) experienced respiratory syncytial virus (RSV) hospitalization rates 5 times higher and an RSV season twice as long as the general US infant population. We describe trends in hospitalization rates and seasonality during 18 years of continuous RSV surveillance in this population and explore contributions of climate and sociodemographic factors. Methods: We abstracted clinical and RSV test information from computerized medical records at YKD Regional Hospital and Alaska Native Medical Center from 1994 to 2012 to determine hospitalization rates and RSV season timing. Descriptive village and weather data were acquired through the US Census and Alaska Climate Research Center, University of Alaska, Fairbanks, respectively. Results: During 1994–2012, YKD infant RSV hospitalization rates declined nearly 3-fold, from 177 to 65 per 1000 infants/yr. RSV season onset shifted later, from mid October to late December, contributing to a significantly decreased season duration, from 30 to 11 weeks. In a multivariate analysis, children from villages with more crowded households and lacking plumbed water had higher rates of RSV hospitalizations (relative rate, 1.17; P = 0.0005 and relative rate, 1.45; P = 0.0003). No association of temperature or dew point was found with the timing or severity of RSV season. Conclusions: Although the RSV hospitalization rate decreased 3-fold, YKD infants still experience a hospitalization rate 3-fold higher than the general US infant population. Overcrowding and lack of plumbed water were associated with RSV hospitalization. Dramatic changes occurred in RSV seasonality, not explained by changes in climate.